Application of Dolomite on The Growth And Yield of Various Rice Genotypes (Oryza sativa L.) Grown on Peat Soil - Rona Tri Madani; Irfan Suliansyah; Benni Satria; Atman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice is the primary staple food for the Indonesian population. However, land use changes have increasingly limited the availability of potential land for rice cultivation. Indonesia possesses vast areas of peatland, which offer significant opportunities for rice extensification. Nonetheless, the acidic and nutrient-poor nature of peat soils necessitates soil improvement efforts through the application of soil ameliorants. Dolomite is one such ameliorant that can enhance the chemical properties of soil and improve nutrient uptake by plants. This study aimed to evaluate the interaction between rice genotypes and dolomite application rates on the growth and yield of several rice genotypes cultivated on peatland. The experiment was conducted from June to December 2024 in Sunur Village, Nan Sabaris District, Padang Pariaman Regency, Indonesia, using a Split Plot Design in a randomized complete block layout with three replications. The results showed that the genotype and dolomite application significantly affected several agronomic parameters, particularly the 1000-grain weight. Genotypes Bujang Marantau and Caredek exhibited superior performance in most yield components. Dolomite application at 10 tons/ha proved to be the most effective dose, enhancing plant growth and productivity under peat soil conditions. These findings offer practical recommendations for optimizing rice production on marginal peatlands and promoting sustainable agricultural development in Indonesia.